Plantation Crop Productivity: Coffee, Sugarcane and Cocoa - Kadir Ruslan; Octavia Rizky Prasetyo (Center for Indonesian Policy Studies (CIPS), 2021)
About a quarter of the plantation sector's Gross Domestic Product (GDP) is contributed by the plantation agriculture sub-sector. However, the plantation sub-sector still faced structural problems such as the relatively low productivity of smallholder plantations compared to that of large plantations run by the government or private sector. Another problem is the quite large disparity of land and labor productivity between regions. Closing the productivity gap is key to enhancing productivity in all these three commodities. In this paper, the writer describes strategies to close the productivity gap between regions and between smallholders and large plantations.
Keywords: 330; Plantation productivity; coffee plantations; cocoa plantations; sugar cane plantations; agriculture; plantation crops; cips policy paper; cips plantation data; kadir ruslan plantations; kadir ruslan; plantation data; improving plantation data; indonesian plantation; agriculture policy; indonesian agriculture data; indonesian plantation data; plantation policy indonesia; food commodity indonesia.